Exit Slips As Predictor of Academic Performance - Raymart Basco (Camarines Sur Polytechnic Colleges, 2021)
Formative assessment plays a vital role in the delivery of quality and relevant education among learners. Data derived from the assessment results provide pieces of evidence for teachers to determine learners who need assistance, advance instructional objectives, track learners' progress toward those standards, and identify what intervention and support are required. This descriptive-survey research examined the impact of exit slips in predicting intermediate pupils' science achievement. Seventy-three pupils were involved in the study who were selected through a total sampling. Weighted mean, ranking, standard deviation, mean percentage score, frequency, Pearson correlation coefficient, and coefficient of determination were utilized to process and analyze statistically the data using SPSS. The findings of the study highlighted that exit slips can help learners in their learning since they reflect pupils' understanding and increase accountability among them. The results revealed that there was a high positive association between the self-rating report and the academic performance of the respondents. The impact of self-reported rating was found significant on the performance of the pupils. Hence, when teachers took necessary and relevant remediation as well as enrichment based on the self-reported rating, academic performance may be improved. It was recommended that teachers may adapt the use of exit slips in their classes to improve academic performance among learners.